2019
DOI: 10.3390/molecules24071231
|View full text |Cite
|
Sign up to set email alerts
|

Concerted Catalysis by Nanocellulose and Proline in Organocatalytic Michael Additions

Abstract: Cellulose nanofibers (CNFs) have recently attracted much attention as catalysts in various reactions. Organocatalysts have emerged as sustainable alternatives to metal-based catalysts in green organic synthesis, with concerted systems containing CNFs that are expected to provide next-generation catalysis. Herein, for the first time, we report that a representative organocatalyst comprising an unexpected combination of 2,2,6,6-tetramethylpiperidine 1-oxyl (TEMPO)-oxidized CNFs and proline shows significantly en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…The chirality-specific orientation and the approach of the substrates to the regularly aligned H-bonding chiral centers on the CNFs were the relevant factors. This phenomenon was emphasized in enantioselective ketone hydrogenation reactions catalyzed by CNC-supported Pd NPs (Kaushik et al 2015) and TOCNFs/proline catalyzed Michael reactions (Ranaivoarimanana et al 2019). Further evidence for the involvement of nanocellulose in the preferential orientation of transition states was provided by quantum mechanics/molecular mechanics/steered molecular dynamics (QM/MM-SMD) in the a b c proline-catalyzed aldol reaction at the surfaces of TOCNFs (Fig.…”
Section: Interfacial Chiral Catalysis On Nanocellulosementioning
confidence: 90%
See 2 more Smart Citations
“…The chirality-specific orientation and the approach of the substrates to the regularly aligned H-bonding chiral centers on the CNFs were the relevant factors. This phenomenon was emphasized in enantioselective ketone hydrogenation reactions catalyzed by CNC-supported Pd NPs (Kaushik et al 2015) and TOCNFs/proline catalyzed Michael reactions (Ranaivoarimanana et al 2019). Further evidence for the involvement of nanocellulose in the preferential orientation of transition states was provided by quantum mechanics/molecular mechanics/steered molecular dynamics (QM/MM-SMD) in the a b c proline-catalyzed aldol reaction at the surfaces of TOCNFs (Fig.…”
Section: Interfacial Chiral Catalysis On Nanocellulosementioning
confidence: 90%
“…In the latter media, the aggregation of nanocellulose is detrimental to aldol reactions (Ellebracht and Jones 2018;Kanomata et al 2018). The presence of water in the system induces limited mass transport and miscibility of the substrates in the vicinity of the fibers, owing to several layers of water molecules that preferentially surround the CNFs and form a hydration shell (Ellebracht and Jones 2018;Ranaivoarimanana et al 2019). Nevertheless, it should be noted that the surface order provided by the crystalline nanocellulose, and the enhanced cooperativity-which are the key factors in superior catalytic activity in such aldol reactions-can overcome the solventrelated issues.…”
Section: Green Organocatalysismentioning
confidence: 99%
See 1 more Smart Citation
“…Natural cellulose, which is the main constituent of plant cell wall, is a chiral homopolymer consisting of D-glucose (denoted as D-cellulose hereafter). This chirality is an important feature of high-value-added D-cellulose applications, such as chiral separation (Francotte 1994, Okamoto and Yashima 1998, D'Orazio et al 2018, Chankvetadze 2020, chiral nematic D-cellulose liquid crystals (Nishio et al 2016, Almedia et al 2018, and D-cellulose-based organocatalysts for asymmetric synthesis (Ikai et al 2011, Yasukawa et al 2015, Ranaivoarimanana et al 2019. Recently, an enantiomer of D-cellulose (denoted as Lcellulose hereafter) consisting of L-glucose was synthesized by our group using cationic ringopening polymerization (Yagura et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…We discovered that the simple addition of TOCNFs to the reaction media drastically improved the catalytic efficiency of proline, a low-performance organocatalyst, in a direct aldol reaction 18 and Michael addition. 19 The striking effects of the nanobrillation and crystallinity of nanocellulose on catalytic performance have clearly indicated that this unique interfacial nanoarchitecture plays an indispensable role in catalytic enhancement.…”
Section: Introductionmentioning
confidence: 99%